2023
DOI: 10.3389/feduc.2023.1136940
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ well-being and their teaching quality during the COVID-19 pandemic: a retrospective study

Abstract: During the COVID-19 pandemic, teachers reported low levels of well-being. Lower levels of well-being can negatively impact job performance and teaching quality. This study aims to examine whether the quality of teaching changed between before and during the pandemic, in two settings: remote and restricted in-person settings, and whether teachers’ well-being was related to the quality of teaching. 279 German-speaking (primary and secondary) teachers were retrospectively surveyed with an online questionnaire. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…There was a positive note in some studies. Sacré et al (2023) found that despite experiencing emotional exhaustion during the pandemic, teachers expressed satisfaction with their occupation. Bailey (2021) found that although the pandemic had worsened certain aspects of precarity for international teachers, some elements of privilege persisted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was a positive note in some studies. Sacré et al (2023) found that despite experiencing emotional exhaustion during the pandemic, teachers expressed satisfaction with their occupation. Bailey (2021) found that although the pandemic had worsened certain aspects of precarity for international teachers, some elements of privilege persisted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is a generalized, positive internal state that can shift with changes in the person or external conditions (Yin et al, 2016). Due to fundamental changes in the teaching process and in working conditions, teacher well-being received considerable research attention during the COVID-19 pandemic and the postpandemic period (Sacré et al, 2023). There was a need to understand and accept changes in teachers' work and to adapt to the changed circumstances.…”
Section: Emotional Resilience and Well-beingmentioning
confidence: 99%
“…Las implicaciones del cambio de modalidad en el bienestar de los profesores, ha sido analizada, por diversos investigadores, como Salcedo et al (2020), Ribeiro et al, (2020), Cortes (2021), Sigursteinsdottir y Rafnsdottir (2022) y Sacre et al (2023), quienes encontraron que el contexto de la emergencia sanitaria afectó la salud mental de los educadores, generando estrés, ansiedad, depresión. agotamiento emocional, entre otros problemas.…”
Section: Introductionunclassified